Research on the Fusion of Power Grid Data and Urban Facilities Data - Tian Jing; Lan Guan; Jin Li; Yanxia Guo; Ao-Sen Li; Youfu Zhang; Zhuangzhuang Yu (E3S Web of Conferences, 2021)
The three-dimensional design of power grid infrastructures needs to consider their adjacent urban facilities, including industrial and civil buildings and tunnels, roads, pipelines, and etc. Therefore, in order to realize the integration of the three-dimensional design model of the power grid and the BIM model of those urban infrastructures, this paper attempts to establish the information model classification and coding method to unify the representation methodology of concepts and technologies of multi-industry infrastructures. The developed data format conversion method and data lightweighting method can be utilized to better integrate the three-dimensional design results of the power grid project with the BIM data of the urban infrastructures, and then these digitalized results of the multi-industry facilities can be used to improve the life-cycle management of the power grid engineering projects.